2021
DOI: 10.1108/he-10-2020-0106
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing health-care service environment with Malaysian general practice clinics

Abstract: PurposeThe purpose of this study is to explore the private general practice (GP) clinics' service environment, patients' satisfaction and their impact on word of mouth (WoM) for others for future treatment in GP clinics.Design/methodology/approachData are collected from 367 respondents using a paper-based survey questionnaire. Partial least square (PLS) is used to evaluate the proposed model and hypotheses relationships.FindingsThe findings reveal that ambience and service delivery have a high significant infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
(74 reference statements)
0
10
0
1
Order By: Relevance
“…The primary aim of an insurance policy is to decrease the risk faced by people in case of unexpected costs of healthcare services, thus hindering one from being adversely affected by financial burden (Owolabi et al, 2016). This stipulates the significance of subscribing to medical care coverage in seek of healthcare services (Rahman, Newaz et al, 2021). Nevertheless, the decision to purchase health insurance is not easy, which is often misconstrued by buyers (Loewenstein et al, 2013) who typically have the right to claim through the insurance policy (Born & Sirmans, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The primary aim of an insurance policy is to decrease the risk faced by people in case of unexpected costs of healthcare services, thus hindering one from being adversely affected by financial burden (Owolabi et al, 2016). This stipulates the significance of subscribing to medical care coverage in seek of healthcare services (Rahman, Newaz et al, 2021). Nevertheless, the decision to purchase health insurance is not easy, which is often misconstrued by buyers (Loewenstein et al, 2013) who typically have the right to claim through the insurance policy (Born & Sirmans, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…PR displayed an insignificant relationship with WTI (hypothesis H 5 ). This is ascribed to the fact that Malaysian working adults are more conscious of HR and PB, rather than the PR of purchasing travel insurance schemes ( 104 ). In a similar vein, Bonnin ( 52 ) identified the relationship between the PR of purchasing a product and the attractiveness of online stores.…”
Section: Discussionmentioning
confidence: 99%
“…The indication echoes the findings of previous studies. 6 , 16 , 17 , 46 , 47 Rahman et al 17 identified the positive significant link between Shariah amenities and satisfaction but there is no available study that examined the direct relationship between Shariah amenities and loyalty. Thus, this is the first to examine the direct negative relationship between Shariah amenities and loyalty.…”
Section: Discussionmentioning
confidence: 99%